LEXICAL-SEMANTIC FIELDS OF WORD-FORMATION ROWS WITH THE SUFFIX -MENT - Olena O. Dotsenko (Alfred Nobel University Journal of Philology, 2022)
The article outlines three lexical-semantic fields of word-formation rows with the suffix -ment. The aim of the paper is to investigate three lexical-semantic fields which consist of the lexical-semantic field denoting improvement, confinement and feelings. To achieve this aim, the following tasks should be completed such as investigating motivation relations in derived words with the suffix -ment and analyzing their structure with the help of the applicative generative model. The methods of componential and comparative analysis and the relator language of the applicative generative model were applied for fulfilling the above-mentioned tasks. To build word-formation rows, the words are segmented according to their motivation relations. Etymological aspect is not taken into account. Every field consists of lexical-semantic groups. The lexical-semantic field denoting the action of improvement consists of fifty-eight words, which are classified into seven lexical-semantic groups. This field is represented by thirteen R-structures. The lexical-semantic field of feelings includes two lexicalsemantic groups which contain six R-structures. The lexical-semantic field of confinement includes twenty-one words represented by six R-structures. Paradigmatic relations in lexical-semantic groups were analyzed in order to illustrate interfiled connections. Synonymic rows and antonymic pairs in lexical-semantic groups and hyperonyms distinguished in lexical-semantic fields prove paradigmatic relations. Lexical-semantic fields consist of nouns because the suffix -ment generates, mainly, nomina actionis. The term word-formation row is described in the paper as this notion which is a complex unit of word-formation hasn’t been studied thoroughly yet. The word-formation row in every lexicalsemantic field is highlighted in the article. The more lexical-semantic groups comprise the lexical-semantic field, the more R-structures the word-formation row has in a lexical-semantic field. Besides, this fact proves that English words with the suffix -ment are polysemous and variable. The polysemy of these words is illustrated via interfiled connections, e.g., the word fulfillment with the meaning “a feeling of satisfaction” belongs to the lexical-semantic field of feelings, and with the meaning “the act of doing smth. that you have promised or intended to do” this word can be involved in the lexical-semantic group of achievement which belongs to the lexical-semantic field of improvement. The relator language of the applicative generative model is used to investigate R-structure of English words with the suffix -ment. This analysis helps to create word-formation rows. R=rows of artificial language and L=rows of natural language are described. The research results lead to the conclusion that three lexical-semantic fields can be characterized by polysemous character of English words with the suffix -ment which are represented by interfiled connections. The variety of R-structures comprising wordformation rows shows the variativity of the investigated words and proves the idea that words may be derived not only from verbs but also nouns and adjectives. Interfield connections in three lexicalsemantic fields demonstrate that all words with the suffix -ment can be grouped into lexical-semantic fields. It can be useful and significant for linguists to create different English dictionaries. So, the aim of the further study is to arrange all existing words with the suffix -ment into lexical-semantic fields and make an attempt to create the dictionary of R-words and L=words with the suffix -ment.